Synthesis Process and Nutritional Evaluation of Plantain as a Supplementary Food for Toddlers in Sierra Leone: A Study Utilizing Biuret’s, Benedict’s, and Iodine Solution Test - Lahai Koroma; James Kuiva Senesie; Florence Wuyah Baion; Baindu Miata Lukulay; Massah Badiwuloi Kallon (Spektra: Jurnal Fisika dan Aplikasinya)
Research on developing plantain fruit into juice, jam, ice cream, and fritters as a food supplement for toddlers was conducted in Sierra Leone. The work was done at the Mosoudo section of Daru village, Jawie Chiefdom, in Kailahun District. Four bunches of plantains were harvested from Jawei Chiefdom and stored in Mosoudo. Two bundles of the raw plantain were peeled, dried, and ground into powder, while the other two left to ripen at room temperature for nine days. Test were conducted using Iodine solution, Benedict solution, and Biuret test to check the presence of starch, glucose, and protein, respectively, in both the powdered and ripe plantain. The ripe plantains were then made into juice, jam, ice cream, and fritters. Fifty  mothers/caregivers, along with their children, were randomly selected to evaluate the color, taste, smell, and texture of the four plantain products. The sensory evaluation results showed high acceptance levels: color (53.5%), taste (59.0%), smell (61%) and texture (59.9%). The results suggest that the project could successfully provide nutritious and appealing food supplements for toddlers in Sierra Leone. It was recommended that the government and NGOs promote the cultivation of plantains instead of importing food supplements for children in Sierra Leone.